Practical Approaches to Family-friendly Medical Studies - Liebhardt, Hubert (German Medical Science GMS Publishing House, 2012)
Based on the pilot study carried out by the Office of the Dean of the Medical University of Ulm on the family-friendliness of the organisation of medical education in Ulm, this paper describes concrete measures that were designed at the university or have been partly implemented already. More flexibility and customization are essential characteristics and prerequisites of a family-friendly medical school as part of university education structures. Flexibility and customization can be achieved by designing lesson plans and study regulations so that both childcare is assured and that in emergencies, help can be quickly offered with a minimum of bureaucracy. More flexibility includes, amongst other things, adequate means for the individual to compensate for missed compulsory attendances and examination dates. The necessary shift in thinking and the willingness to cooperate on behalf of the management and teaching staff can be supported through the audit for family-friendliness “berufundfamilie” (job and family) or “familiengerechte hochschule” (family-friendly university), as well as strategic management tools of family-friendly corporate policies. Supporting mechanisms such as effectively networked advice services, course progression monitoring based on data, providing a parents’ passport with a cross-semester training contract, creating more interaction between student-parents or other students through a parent community or by study pairings and finally, reliable information on and compliance with the maternity leave rules for pregnant and breastfeeding medical students can help safeguard successful studying with children.